2015
DOI: 10.5812/jjm.24298
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility Patterns of Candida Species Isolated From Urine Samples to Posaconazole and Caspofungin

Abstract: Background:Candiduria is a rising condition among hospitalized patients and Candida albicans is the most common recovered agent. However, non-albicans Candida species (NACs) such as C. glabrata, C. krusei, C. parapsilosis, and C. tropicalis are also important. Although most Candida species especially C. albicans are sensitive to routinely used antifungals, an increasing trend in resistance has been observed among NACs.Objectives:The aim of the present study was to detect the susceptibility of Candida strains r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
3
13
1
1
Order By: Relevance
“…As already mentioned in most studies, among Candida species, C. albicans, C. parapsilosis, C. tropicalis, C. glabrata, and C. krusei were the most common causes of candidiasis in Iran. Several studies showed that Candida onychomycosis was the predominant yeast infection (2,5,19,21), consistent with the current study results (41.8%). In the current study, the most prevalent species isolated from clinical samples was C. albicans, followed by C. parapsilosis, C. tropicalis, and C. guilliermondii.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As already mentioned in most studies, among Candida species, C. albicans, C. parapsilosis, C. tropicalis, C. glabrata, and C. krusei were the most common causes of candidiasis in Iran. Several studies showed that Candida onychomycosis was the predominant yeast infection (2,5,19,21), consistent with the current study results (41.8%). In the current study, the most prevalent species isolated from clinical samples was C. albicans, followed by C. parapsilosis, C. tropicalis, and C. guilliermondii.…”
Section: Discussionsupporting
confidence: 93%
“…In epidemiological studies, most of the yeast isolates belong to Candida species, especially C. albicans (1,4,5,17,18). Previous studies in different regions of Iran show that Candida species were isolated from various clinical samples rather than other yeasts (2,5,(18)(19)(20)(21)(22)(23). As already mentioned in most studies, among Candida species, C. albicans, C. parapsilosis, C. tropicalis, C. glabrata, and C. krusei were the most common causes of candidiasis in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a POS MIC90 value of 0.06 μg/ml was reported in C. albicans and 2 μg/ml for C. glabrata isolates in Castanheira et al [ 13 ]. In Mahmoudabadi et al 94% of the isolates were inhibited by POS at < 2 μg/mL after 24 h, whereas 6% of isolates had MICs of > 4 μg/mL [ 20 ]. According to the present study, the ECV and MIC90 values of POS in C. krusei were 0.5 μg/ml, and POS is the best antifungal agent for the treatment of infections due to this species.…”
Section: Discussionmentioning
confidence: 99%
“…Espinel-Ingrof et al reported that CAS MICs value evaluation for some Candida species (such as C. glabrata and C. krusei according to CLSI breakpoints is not suitable and could lead to reporting an excessive number of wild-type or non-wild type isolates [ 23 ]. In Mahmoudabadi et al the MIC of CAS in 90% of the total INFECT Candida isolates was lower than 2 μg/mL [ 20 ]. In Abad et al MIC values for CAS in C. albicans , C. parapsilosis complex, C. tropicalis , C. glabrata complex, C. guilliermondii and C. krusei were reported as 0.008 μg/ml, 2 μg/ml, 0.12 μg/ml, 0.12 μg/ml, 2 μg/ml, and 0.5 μg/ml, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, C. tropicalis 3.9%, C. parapsilosis 4.9%, C. dubliniensis 1.5%, and no C. kefyr were reported (18). Another study revealed the rates of non-albicans Candida were C. krusei (14%), C. tropicalis (16%), and C. glabrata (24%) (19). The existing differences in the distributions may be due to differences in the places where the studies were conducted.…”
Section: Discussionmentioning
confidence: 97%